Theoretical and experimental determination of K - And L -shell x-ray relaxation parameters in Ni - Guerra, Mauro (2019)
M. Guerra acknowledges the support of the FCT, under Contract No. SFRH/BPD/92455/2013. This work was supported in part by the research center Grants No. UID/FIS/04559/2013 to LIBPhys-UNL, and No. UID/MULTI/04046/2013 to BioISI, from the FCT/MCTES/PIDDAC. Laboratoire Kastler Brossel is "Unite Mixte de Recherche du CNRS, de l' ENS et de l'UPMC" No. 8552. Parts of this work have been carried out in the framework of the Project 14IND01 3DMetChemIT, funded by the EMPIR program, co-financed by the Participating States and from the European Union's Horizon 2020 research and innovation program.